Advancement of the DLR TAU Code Method to Simulate Two-phase Flow with Phase-change at the Interface with Applications in Upper Stages of Space Launch Systems - Keiderling, David; Justus Liebig University Giessen (My University, 2023)
The presented thesis discusses work that has been conducted to extend the German Aerospace Center (DLR) TAU Code to simulate heat and mass transfer in two-phase systems in launcher cryogenic upper stages. Preceding work has been performed to extend the incompressible version of the DLR in-house Computational Fluid Dynamic Code TAU to simulate isothermal two-phase flows. A Volume of Fluid approach and a finite volume discretization are used. Due to the grid handling in TAU, an algebraic solution of the interface position was necessary and implemented yielding shorter computation times compared to geometrical approaches on both structured and unstructured grids. This model was extended to simulate heat and mass transfer over the two-phase interface. The work includes updating the energy equation, the mass conservation equation and adapting the respective numerical simulation. Density deviations are included via the Boussinesq-approximation and heat convection is modelled by Fouriers law. The resulting changes were then tested and validated using basic test-cases and a complex use case of the stratification process within a dewar filled with liquid and gaseous hydrogen. The achieved results are presented in this work. Generally, an agreement for the validation test cases with the analytical results were found although some issues with curved interfaces remained. The implementation was also able to simulate the complex test case of stratification, yielding compatible results when compared to the experimental data that has been provided to analyze the simulations.
Keywords: DLR TAU Code; Launcher; Volume of Fluid; Phase Change; CFD; Stratification; ddc:500; ddc:530; ddc:620